Modern banking - Heffernan, Shelagh A. (Chichester, West Sussex, England ; Hoboken, NJ : John Wiley & Sons, 2005)
Modern banking focuses on the theory and practice of banking, and its prospects in the new millennium. The key issues covered in the book include: the core banking functions; different types of banks and diversification of bank activities; risk management: issues and techniques; global regulation: basal1 and 2; bank regulation in the UK, US, EU and japan; banking in emerging markets; bank failure and financial crises; competitive issues from cost efficiency to mergers and acquisition and case studies.
Includes bibliographical references (p. [653]-681) and index.
nmn 17/05/13
Loans
Keywords: Banks and banking; Modern banking